The MEGaN project: I. Missing formation of massive nuclear clusters and tidal disruption events by star clusters-massive black hole interactions - Arca Sedda, Manuel; Capuzzo-Dolcetta, Roberto (Monthly notices of the Royal Astronomical Society, 2017)
We investigated the evolution of a massive galactic nucleus hosting a supermassive black hole (SMBH) with mass MSMBH = 108 M ⊙ surrounded by a population of 42 heavy star clusters (globular clusters, GCs). Using direct N-body modelling, we show here that the assembly of a nuclear star cluster (NSC) through GC orbital decay and merger is efficiently inhibited by the tidal forces exerted from the SMBH. The GC mass-loss induced by tidal forces causes a significant modification of their mass function, leading to a population of low-mass (<104) clusters. None the less, the GC debris accumulated around the SMBH give rise to well-defined kinematical and morphological properties, leading to the formation of a disc-like structure. Interestingly, the disc is similar to the one observed in the M31 galaxy nucleus, which has properties similar to our numerical model. The simulation produced a huge amount of data, which we used to investigate whether the GC debris deposited around the SMBH can enhance the rate of tidal disruption events (TDEs) in our galaxy inner density distribution. Our results suggest that the GC disruption leads to a TDE rate of ∼2 × 10−4 yr−1, about an order of magnitude larger than observed in galactic nuclei with similar density profiles and central SMBH. Our results suggest that the GC disruption shapes the SMBH neighbourhoods, leading to a TDE rate of ∼2 × 10−4 yr−1, a value slightly larger than what expected in previous theoretical modelling of galaxies with similar density profiles and central SMBHs. The simulation presented here is the first of its kind, representing a massive galactic nucleus and its star cluster population on scales ∼100 pc.
Gesehen am 17.10.2017